Do We Need to Rethink the Epidemiology and Healthcare Utilization of Parkinson's Disease in Germany? - Heinzel, Sebastian; Berg, Daniela; Binder, Sebastian; Ebersbach, Georg; Hickstein, Lennart; Herbst, Heinz; Lorrain, Michael; Wellach, Ingmar; Maetzler, Walter; Petersen, Gudula; Schmedt, Niklas; Volkmann, Jens; et al. (Frontiers in Neurology, 2018)
Epidemiological aspects of Parkinson’s disease (PD), co-occurring diseases and medical healthcare utilization of PD patients are still largely elusive. Based on claims data of 3.7 million statutory insurance members in Germany in 2015 the prevalence and incidence of PD was determined. PD cases fulfilled had at least one main hospital discharge diagnosis of PD, or one physician diagnosis confirmed by a subsequent or independent diagnosis or by PD medication in 2015. Prevalence of (co-)occurring diseases, mortality, and healthcare measures in PD cases and matched controls were compared. In 2015, 21,714 prevalent PD cases (standardized prevalence: 511.4/100,000 persons) and 3,541 incident PD cases (standardized incidence: 84.1/100,000 persons) were identified. Prevalence of several (co-)occurring diseases/complications, e.g. dementia (PD/controls: 39%/13%), depression (45%/22%), bladder dysfunction (46%/22%), and diabetes (35%/31%), as well as mortality (10.7%/5.8%) differed between PD and controls. The annual healthcare utilization was increased in PD compared to controls, e.g. regarding mean±SD physician contacts (15.2±7.6/12.2±7.3), hospitalizations (1.3±1.8/0.7±1.4), drug prescriptions (overall: 37.7±24.2/21.7±19.6; anti-PD medication: 7.4±7.4/0.1±0.7), assistive/therapeutic devices (47%/30%), and therapeutic remedies (57%/16%). The standardized prevalence and incidence of PD in Germany as well as mortality in PD may be substantially higher than reported previously. While frequently diagnosed with co-occurring diseases/complications, such as dementia, depression, bladder dysfunction and diabetes, the degree of healthcare utilization shows large variability between PD patients. These findings encourage a rethinking of the epidemiology and healthcare utilization in PD, at least in Germany. Longitudinal studies of insurance claims data should further investigate the individual and epidemiological progression and healthcare demands in PD.